One Year Data of New Secondary Glaucoma Patients at Top Referral Eye Hospital in Indonesia - Rifqah, Elka; Gustianty, Elsa; Prajitno, Ihrul Prianza (Althea Medical Journal, 2017)
Background: Glaucoma is the second most common cause of blindness after cataract in the world and also in Indonesia. Based on the etiology, glaucoma is classified into primary and secondary glaucoma. Secondary glaucoma can cause severe visual function disorders and affect the patientâs quality of life. This study was carried out to indentify the characteristics of new secondary glaucoma patients at Cicendo Eye Hospital from January to December 2013. Methods: This descriptive study was carried out at Cicendo Eye Hospital from November to December 2014. Secondary data were retrieved from medical records of new secondary glaucoma patients who came to the Glaucoma unit from January to December 2013. Inclusion criteria were medical records comprising data about age, gender, location of the affected eyes by secondary glaucoma, etiology of secondary glaucoma and value of intraocular pressure. The collected data were recorded and analyzed toÂ  illustrate their frequency distribution and proportion.Results: Out of 63 patients, 42.9% was 40â59 years old and 63.5% was men. Most cases were unilateral (82.5%). It was found that 74 eyes (52 unilateral, 11 bilateral), diagnosed as secondary glaucoma, had intraocular pressure â¥30 mmHg which were 54.1%. Secondary glaucoma were caused by lens induced (36.5%), inflammation (22.2%), and trauma (9.5%).Conclusions: Most cases are middle-aged patients and dominated by men. The eye diagnosed as secondary glaucoma occurred more in the unilateral eye which has intraocular pressure â¥30 mmHg and is caused by lens induced and inflammation.Â DOI:Â 10.15850/amj.v4n2.1060